Dakwah Melalui Boneka (Studi pada Ustadzah Lulu Susanti) - Nanda Elma Fitriani; Lina Amiliya (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2023)
The purpose of this study was to find out the proselytizing strategy carried out by Ustadzah Lulu Susanti with puppet media. Modern society that tends to be pragmatic is also inseparable from the target of da'i. However, people tend to like a unique treat in proselytizing, namely using the medium of proselytizing.  This research method uses qualitative with a descriptive approach. The primary data in this study was obtained by looking at the proselytizing carried out by Ustadzah Lulu Susanti in the media. Meanwhile, secondary data in this study were obtained from literature studies, journals, and other documents needed for the preparation of this article. This data analysis technique uses the Miles and Huberman Model with data reduction, data presentation, and conclusion drawing. The results of this study show that Dolls are one of the proselytizing media used by Ustadzah Lulu Susanti in delivering her syiar. This will certainly attract the attention of mad'u, especially among children. Thus, the treat of proselytizing becomes the satisfaction of mad'u who listens to the proselytizing. Ina is a doll name used in delivering proselytizing by Ustadzah Lulu which is able to attract a lot of attention from the public.